Legal Pluralism and Muslim Family Authority in Sustaining Female Circumcision in Serang, Indonesia: A Critical Documentary Analysis - Parta Suhanda; Siti Na Jauharoh; Ema Hikmah; Ida Lindawati; Kamall Aly (Universitas Muhammadiyah Bandung, 2025)
Women's circumcision in Serang, Banten, is in a space of legal pluralism that brings together religious, customary, family, health, and state regulatory norms. Previous research has generally examined these practices from the perspective of public health, gender, religion, anthropology, or law in isolation, so it has not explained how these various normative arrangements are mediated in family decision-making. This study aims to analyze the social reproductive mechanisms of female circumcision practices through the development of a Family-Mediated Socio-Legal Reproduction Model. The research uses a qualitative socio-legal approach with critical documentary analysis and thematic synthesis of academic literature, laws and regulations, government policies, public health reports, and religious publications relevant to the Indonesian context, especially Banten. The results of the study show three main findings. First, Muslim families reproduce female circumcision as a symbol of purification, honor, and femininity, even though it has no medical indications. Second, the distribution of authority in the family along with the symbolic position of the paraji shaman transforms religious and customary norms into ritual practices that gain social legitimacy. Third, regulatory fragmentation, differences in definitions of harm, and weak integration between legal and health approaches reduce the effectiveness of state interventions and biomedical evidence. This study also identifies paraji shamans as socio-legal actors who act as cultural intermediaries, holders of symbolic authority, and implementers of local health governance. The findings expand the study of legal pluralism by showing that the effectiveness of legal, medical, religious, and customary norms depends on the mediation process in the family and community. Therefore, prevention strategies require the integration of legal protection, family-based health education, the involvement of traditional practitioners, and the strengthening of religious narratives that place bodily dignity, child protection, and harm prevention as the main principles.